Analisis Lintasan Terbang Roket Model Satu Tingkat Dengan Berbantuan Perangkat Lunak - Tri Susilo; Aris Widodo (Jurnal Teknologi Kedirgantaraan, 2020)
This paper provides an explanation of the computational and analyses of flight line for single stage rocket model. There are two software’s used are that Visual Basic 6.0 to flight line analytic and MatCad 2000 to get the figure of position and flight history. The rocket analyses are including the maximum flight altitude, velocity, position, mass comparison, jet velocity, specific and total impulse on every altitude. The conclusion obtained is that the Rocket reaches its highest point (culmination point) at an altitude of 31,589.66 meters within 178.13 seconds after the rocket starts launching. The rocket section at an altitude of 17,772.49 meters in 11.23 seconds will experience a dead spot and will glide at Voff speed to the peak point (culmination point).